2017
DOI: 10.1515/ijb-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Four Methods for Estimating Tree-Based Treatment Regimes

Abstract: When multiple treatment alternatives are available for a certain psychological or medical problem, an important challenge is to find an optimal treatment regime, which specifies for each patient the most effective treatment alternative given his or her pattern of pretreatment characteristics. The focus of this paper is on tree-based treatment regimes, which link an optimal treatment alternative to each leaf of a tree; as such they provide an insightful representation of the decision structure underlying the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…These methods have different objectives and there is not yet an agreed-upon single best method. In a simulation study, Sies and Van Mechelen (2016) found the method of Zhang et al (2012a) to perform best, followed by MOB. However, the method of Zhang et al performed worst under some conditions of the simulation study in terms of the type I error rate.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…These methods have different objectives and there is not yet an agreed-upon single best method. In a simulation study, Sies and Van Mechelen (2016) found the method of Zhang et al (2012a) to perform best, followed by MOB. However, the method of Zhang et al performed worst under some conditions of the simulation study in terms of the type I error rate.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Therefore, our comparative study focuses on a selection criterion appropriate from a regulatory point of view. Other comparisons are based on a single dataset, evaluate the estimation of tree‐based treatment regimes or focus on identifying covariates affecting treatment effects rather than identifying subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous methods for this purpose available, comparisons of methods applicable to similar settings are lacking, with the notable exceptions of articles by Doove et al, Alemayehu et al, and Sies and Mechelen . Boulesteix et al point out that more neutral comparison studies, which evaluate the behavior of existing methods, are needed.…”
Section: Introductionmentioning
confidence: 99%
“…' It is mainly the latter type of interaction that matters in personalized medicine [38]. Only recently, however, important methodological developments have been made for a statistical method that focuses on https://doi.org/10.1016/j.pmip.2019.100054 qualitative interaction [25,33]. Qualitative interaction trees (QUINT) is one such method recently developed by Dusseldorp et al [9,10].…”
Section: Introductionmentioning
confidence: 99%